Adaptive Full-Duplex and Half-Duplex Power Line Relay and Power Optimization Allocation Algorithm - Zhixiong CHEN; Honghai ZENG; Dongsheng HAN (Zhongguo dianli)
In order to improve the long-distance communication capability, power line communication currently mainly adopts a two-slot half-duplex relay technology. Full-duplex technology can improve the spectral efficiency and solve electromagnetic interference problems of the system, but its performance is prone to be affected by self-interference. The paper proposes a full-duplex and half-duplex adaptive power line relay algorithm and analyzes its system performance. Based on the power line channel model of lognormal fading and Bernoulli-Gaussian impulse noise, the signal processing process of different duplex and adaptive relay steps are given. Then, using Gauss-Hermite transform and sub-regional integration, the outage probability in different duplex modes is derived. After that, the reliability of the theoretical formula is verified by Monte Carlo simulation. The impact of duplex mode, self-interference, relay location, power and channel parameters on system performance are analyzed. Finally, the optimal power allocation value is obtained by the sequential quadratic programming.